Mitigating time-dependent crack growth in Ni-base superalloy components. (January 2016) - Chan, Kwai S.; Enright, Michael P.; Moody, Jonathan; Fitch, Simeon H.K.
Highlights: Develop a methodology to treat cycle- and time-dependent crack growth. Model the effects of tertiary γ ′ and grain size on time-dependent crack growth. Treat small-scale creep, oxidation, and stress relaxation at the crack tip. Reduce the risk of fracture of a gas turbine disk via microstructural control. Large grain size and tertiary γ ′ size at the rim extend disk life and reduce risk. Abstract: Advanced Ni-based gas turbine disks are expected to operate at higher service temperatures in aggressive environments for longer time durations. Exposures of Ni-base alloys to these aggressive environments can lead to cycle-dependent and time-dependent crack growth in superalloy components for advanced turbopropulsion systems. In this article, the effects of tertiary γ ′ on the crack-tip stress relaxation process, oxide fracture and time-dependent crack growth kinetics are treated in a micromechanical model which is then incorporated into the DARWIN® probabilistic life-prediction code. Using the enhanced risk analysis tool and material constants calibrated to powder-metallurgy (PM) disk alloy ME3, the effects of grain size and tertiary γ ′ size on combined time-dependent and cycle-dependent crack growth in a PM Ni-alloy disk is demonstrated for a generic rotor design and a realistic mission profile using DARWIN. The results of this investigation are utilized to assess the effects of controlling grain size and γ ′ size on the risk of disk fracture and to identify possible means for mitigating time-dependent crack growth (TDCG) in hot-section components.